Implementasi Algoritma Additive Code Untuk Mengkompresi File PDF Pada Aplikasi E-Archive - Ningsih, Fitri Ayu (CV. Graha Mitra Edukasi, 2024)
Problems with the need for storage space in the E-Archive application is one of the main problems that can affect the performance of own E-Archive application. This is due to the large number of PDF files large files stored in the E-Archive application database. One of solutions that can be done to overcome this problem are compress PDF files. The compression process in this study was carried out based on an algorithm Additive Code. Based on the results of the tests performed, the Ratio of Compression (RC) of 1.33, Compression ratio (Cr) reduced by as much 75%, Redundancy (Rd) is reduced by 25% and Space saving (Ss) is reduced as much as 25%. The results show that the need for storage space the E-Archive application database is more optimal than before the process was implemented compression.